PENERAPAN PENDEKATAN KONTEKSTUAL ELEMEN INKUIRI DALAM MENULIS LAPORAN OLEH SISWA KELAS VIII SMP SWASTA MARISI MEDAN HELVETIA TAHUN PEMBELAJARAN 2012/2013 - MERRYDONNA CHRISTINA SIMANGUNSONG (Basastra, 2012)
The application of approach contextual element inquiri in study write report by student class of VIII SMP private sector of Marisi Medan Helvetia year study 2012/2013. This study aimed to describe the difference of study result write report applying of approach contextual element inquiri and without applying approach contextual element inquiri. Population in this research is all class student of VIII SMP private sector of Marisi Medan Helvetia year study 2012/2013. This research sampel is 30 people from 110 existing population. This research use experiment method of pre-test design group one post test that is experiment which do not use comparator group. From data processing obtained by result of pre test with mean = 68.86, standard of deviasi = 10.33, standard of error = 1.92 and including at category very good counted 1 student or 3.33%, good category counted 12 student or 40%, category enough counted 15 student or 50%, and category less counted 2 student or 6.66%. Result of post test with mean = 81.11, standard of deviasi 10.78%, and standard of error = 2.00. Including at category very good counted 5 student or 16.66%, good category counted 23 student or 76.66%, and category enough counted 2 student or 6.66%. From data test result of and pre-test of post-test got result normal distribution. Of homogeneity test got that this research sampel come from homogeneous population. After test of normalitas, got by t0 equal to 4.38. Then, t0 consulted with tables of t level of signifikasi 5% with df=N-1=30-1=29, obtained by level of signifikasi 5% = 2.04. Because obtained t0 bigger than t that is 8.57 > 2.04. so, nul hypothesis (Ho) refused and hypothesis (Ha) accepted. Finally, can be concluded that there are difference which signifikasi between result of study write report applying of approach contextual element inquiri with result of study write report without applying of approach contextual element inquiri by class student of VIII SMP private sector of Marisi Medan Helvetia year study 2012/2013.   Keywords: approach contextual, inquiri, writing report.